Identifying the Adaptability of Different Control Types Based on Delay and Capacity for Isolated Intersection. Issue 3 (March 2023) - Danesh, Ali; Ma, Wanjing; Wang, Ling
In urban road networks, intersections are the main bottlenecks. Selecting an appropriate intersection control type can significantly improve the performance of an isolated intersection. Therefore, this paper offers recommendations for selecting the most efficient control type among two-way stop control, signalized intersection (SIG), roundabout (RB), and signalized roundabout (SIGRB) based on capacity and delay. The procedure to calculate delay and capacity is taken from the Highway Capacity Manual 6th edition (2016), or developed separately if needed. Two flow patterns are assumed: fixed and time-varying demand. For fixed demand, the results show that SIGRB outperforms other control types both in capacity and delay at higher demand levels. It was also observed that increase in left-turn ratio increases the delay and decreases the capacity of all control types while its impact on SIGRB was the least. Considering time-varying demand, traffic volume fluctuates over the 5-h period of the analysis. It was found that using both RB and SIGRB together creates significantly less delay compared with the other options. Additionally, using RB provides less variability in delay when there is fluctuation in demand. The major finding of this research is that RB and SIGRB have potential benefits for delay in conditions of (i) high traffic volume, (ii) high left-turn ratio, and (iii) demand fluctuation. Furthermore, it is suggested that SIG should be used if the left-turn ratio is relatively low. The results of this study could help decision-makers to choose the best control type for an isolated intersection under various traffic conditions.